A challenge of inactivity after the COVID-19 pandemic: What can we learn from Australia? - Boliang Wang; Qin Sun; Xiaorui Xing; Tiemin Liu; Ru Wang (Advanced Exercise and Health Science)
This article discusses the importance of resuming exercise and physical activity (PA) post-COVID-19 pandemic, drawing insights from Australia's experience as a reference point. In Australia, accredited exercise physiologists (AEP) collaboratively work within their health sectors, employing evidence-based guidelines to assist individuals in safely resuming PA and exercise. Based on the latest guideline from Exercise and Sports Science Australia (ESSA) for AEP, tailored for post-pandemic PA resumption, the article summarizes what exercise professionals could do during this period in the wake of COVID-19 disruptions. Using China as a focal example, the article further explores potential interventions and approaches from both public health and clinical perspectives. The discourse concludes by emphasizing the worldwide-recognized importance of establishing regulatory bodies akin to ESSA and advancing clinical exercise physiology courses, highlighting their potential in global post-pandemic recovery efforts.